Pengaruh Net Ekspor, Kurs, Foreign Direct Invesment dan Wisatawan Asing terhadap Cadangan Devisa di Indonesia - Karimi, Arief Farhan; Maryanti, Maryanti; Karimi, Kasman (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
This research aims to analyze the influence of Net Exports, Exchange Rates, Foreign Direct Investment (FDI), and the number of foreign tourists on Foreign Exchange Reserves in Indonesia. The data used in this study is secondary data sourced from the World Bank website and the Central Statistics Agency. The data analysis method used is Multiple Linear Regression (time series) in Indonesia over 30 years from 1994 to 2023. Based on the analysis results, it is known that exchange rates and FDI have a significant and positive influence on foreign exchange reserves, while net exports and the number of foreign tourists have an insignificant and positive influence on foreign exchange reserves in Indonesia.